2003
DOI: 10.1097/00006982-200302000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating Keratoplasty Surgery Combined With Vitrectomy After Failing Previous Corneal Surgery

Abstract: The outcome was poor in eyes with goniosynechia and ocular hypotony, and combined surgery is not indicated for either anatomic or visual preservation in such cases. Care should be taken not to overlook intraocular infection in patients undergoing immunosuppressive therapy against graft rejection. The early detection of retinal detachment is also important in eyes exhibiting hypotony after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…11 The rate of development of endophthalmitis in patients with MK has been reported to be in the range of 0.7% to 1.7% and often carries a poor visual prognosis. 5 Most other studies on combined MK and endophthalmitis have reported bacterial growth only. Any discontinuity in the posterior capsule provides a tract for the microbes to travel to the posterior segment even with a trivial anterior segment infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 The rate of development of endophthalmitis in patients with MK has been reported to be in the range of 0.7% to 1.7% and often carries a poor visual prognosis. 5 Most other studies on combined MK and endophthalmitis have reported bacterial growth only. Any discontinuity in the posterior capsule provides a tract for the microbes to travel to the posterior segment even with a trivial anterior segment infection.…”
Section: Discussionmentioning
confidence: 99%
“…Visual rehabilitation is often difficult and of secondary consideration. 5 Their series had seven cases of fungal endophthalmitis. 10 The prognosis becomes much poorer if it is associated with microbial keratitis or corneal opacification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If PKP is performed on such eyes, the success rate will dramatically be reduced due to insufficient nourishment of the cornea, which is caused by an inadequate aqueous flow and an unavoidable silicone oil-endothelium contact [911]. Roters et al [3] reported a series of 34 severely injured eyes that underwent the PPV + TKP + PKP procedure; 8 eyes were considered phthisical and 10 eyes had a longstanding hypotony.…”
Section: Discussionmentioning
confidence: 99%